Serum bile acids as a prognostic biomarker in biliary atresia following Kasai portoenterostomy. Issue 3 (17th March 2023) - Harpavat, Sanjiv; Hawthorne, Kieran; Setchell, Kenneth D. R.; Rivas, Monica Narvaez; Henn, Lisa; Beil, Charlotte A.; Karpen, Saul J.; Ng, Vicky L.; Alonso, Estella M.; Bezerra, Jorge A.; Guthery, Stephen L.; Horslen, Simon; et al.
Abstract : Background and Aims: In biliary atresia, serum bilirubin is commonly used to predict outcomes after Kasai portoenterostomy (KP). Infants with persistently high levels invariably need liver transplant, but those achieving normalized levels have a less certain disease course. We hypothesized that serum bile acid levels could help predict outcomes in the latter group. Approach and Results: Participants with biliary atresia from the Childhood Liver Disease Research Network were included if they had normalized bilirubin levels 6 months after KP and stored serum samples from the 6‐month post‐KP clinic visit ( n  = 137). Bile acids were measured from the stored serum samples and used to divide participants into ≤40 μmol/L ( n  = 43) or >40 μmol/L ( n  = 94) groups. At 2 years of age, the ≤40 μmol/L compared with >40 μmol/L group had significantly lower total bilirubin, aspartate aminotransferase, alanine aminotransferase, gamma‐glutamyltransferase, bile acids, and spleen size, as well as significantly higher albumin and platelet counts. Furthermore, during 734 person‐years of follow‐up, those in the ≤40 μmol/L group were significantly less likely to develop splenomegaly, ascites, gastrointestinal bleeding, or clinically evident portal hypertension. The ≤40 μmol/L group had a 10‐year cumulative incidence of liver transplant/death of 8.5% (95% CI: 1.1%–26.1%), compared with 42.9% (95% CI: 28.6%–56.4%) for the >40 μmol/L group ( p  = 0.001). Conclusions: Serum bile acid levels may be a useful prognostic biomarker for infants achieving normalized bilirubin levels after KP. Abstract :